2017
DOI: 10.1097/ta.0000000000001449
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between factor (F)XIa, FIXa and tissue factor and trauma severity

Abstract: BACKGROUND It has been observed that trauma patients often display elevated procoagulant activity that could be caused, in part, by tissue factor (TF). We previously observed that trauma patients with thermal, blunt and penetrating injuries have active FIXa and FXIa in their plasma. In the current study we evaluated the effect of injury severity, with or without accompanying shock, on the frequency and concentration of TF, FIXa and FXIa in plasma from trauma patients. METHODS Eighty trauma patients were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
3
12
0
Order By: Relevance
“…Indeed, we observed in a previous study that the majority of trauma patients have both TF and FXIa present in plasma. 15 Similar results related to FXIa and TF activity were also obtained for patients with inflammatory bowel disease 16 and various cardiovascular diseases, 17 18 19 especially those with acute coronary syndrome, which have active FXIa in their plasma for which the concentrations correlates with markers of inflammation and thrombin generation. 17 A significant fraction of those patients also had detectable TF activity, which, most likely, could be assigned to TF presented on microparticles.…”
Section: Introductionsupporting
confidence: 60%
“…Indeed, we observed in a previous study that the majority of trauma patients have both TF and FXIa present in plasma. 15 Similar results related to FXIa and TF activity were also obtained for patients with inflammatory bowel disease 16 and various cardiovascular diseases, 17 18 19 especially those with acute coronary syndrome, which have active FXIa in their plasma for which the concentrations correlates with markers of inflammation and thrombin generation. 17 A significant fraction of those patients also had detectable TF activity, which, most likely, could be assigned to TF presented on microparticles.…”
Section: Introductionsupporting
confidence: 60%
“…In several previously published studies we observed an endogenous procoagulant activity present in plasma of cardiovascular and trauma patients and in plasma of patients with inflammatory diseases (10, 18, 3335). This activity is caused by the presence of either functional TF or active FXIa or FIXa, or by any combination of these 3 proteins.…”
Section: Discussionmentioning
confidence: 69%
“…CTI, an inhibitor of FXIIa (20), efficiently prevents thrombin generation in PCPS-containing plasma from healthy individuals in the absence of TF (10) because TG is triggered by the contact pathway. Based on the previously published data (16) and on the data of this study, CTI inhibits thrombin generation in whole blood as well.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations